Interdire, documenter, patrimonialiser. Les chants kapiwaya sous le regard colonial et post-colonial (Nord-Ouest de l’Amazonie, de 1883 à nos jours) - Emilio Frignati (Caravelle)
This article takes a look at the history of the colonial and post-colonial gaze on the kapiwaya, a register of indigenous ritual dances and songs widespread in northwestern Amazonia. It shows that the current patrimonialisation of the kapiwaya and the relative debates are a continuation to the representations and practices promoted by missionaries, soldiers and politicians since the end of the 19th century. Although these ways of giving shape to the songs and dances have in common the occultation of the indigenous point of view on the kapiwaya, they become an arena where the political recognition of indigenous peoples is played out.